Durkheim in dialogue: A centenary celebration of the elementary forms of religions life - Hausner, Sondra L. (New York Berghahn Books, 2017)
One hundred years after the publication of the great sociological treatise, The Elementary Forms of Religious Life, this new volume shows how aptly Durkheim' s theories still resonate with the study of contemporary and historical religious societies.